2003
DOI: 10.1083/jcb.200210057
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Cδ4 is required for Ca2+ mobilization essential for acrosome reaction in sperm

Abstract: Zona pellucida (ZP)–induced acrosome reaction in sperm is a required step for mammalian fertilization. However, the precise mechanism of the acrosome reaction remains unclear. We previously reported that PLCδ4 is involved in the ZP-induced acrosome reaction in mouse sperm. Here we have monitored Ca2+ responses in single sperm, and we report that the [Ca2+]i increase in response to ZP, which is essential for driving the acrosome reaction in vivo, is absent in PLCδ4−/− sperm. Progesterone, another physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(120 citation statements)
references
References 48 publications
2
115
2
1
Order By: Relevance
“…The spatiotemporal pattern of [Ca 2C ] i changes observed in this study is apparently different from the one reported in mouse (Fukami et al 2003), though as yet the [Ca 2C ] i in the entire flagellum of mouse sperm has not been reported. Fukami et al (2003) showed that progesterone initiates an increase in the (Lishko et al 2011, Strunker et al 2011. Interestingly, mouse CatSper does not seem to be activated by progesterone (Lishko et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…The spatiotemporal pattern of [Ca 2C ] i changes observed in this study is apparently different from the one reported in mouse (Fukami et al 2003), though as yet the [Ca 2C ] i in the entire flagellum of mouse sperm has not been reported. Fukami et al (2003) showed that progesterone initiates an increase in the (Lishko et al 2011, Strunker et al 2011. Interestingly, mouse CatSper does not seem to be activated by progesterone (Lishko et al 2011).…”
Section: Discussioncontrasting
confidence: 52%
“…Although CatSper is not activated by progesterone in mouse sperm, progesterone somehow elicits the Ca 2C transient in these cells even from CatSper1-null mice (Ren et al 2001, Fukami et al 2003. This fact suggests that progesterone might activate another Ca 2C influx pathway besides CatSper in mammalian sperm.…”
Section: Discussionmentioning
confidence: 90%
“…Calcium is a key molecule in the regulation of AR and hyperactivation by steroid hormones (Luconi et al 1999, Baldi et al 2000, 2009, Noguchi et al 2008, Fujinoki 2009). After progesterone binds to the sperm head, it stimulates calcium influx and activation of PLC (Fukami et al 2003, Lö sel & Wehling 2003, Harper et al 2004, Luconi et al 2004, Noguchi et al 2008, Baldi et al 2009, Fujinoki 2009). Moreover, spermatozoa are not hyperactivated in the mTALP medium without calcium (Fujinoki 2008, Noguchi et al 2008.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested that progesterone binds to the acrosome region, and PGR is localized to the same region in human (Gadkar et al 2002) and hamster spermatozoa (Noguchi et al 2008). Phospholipase C (PLC; Fukami et al 2003) and/or protein kinase A (Harrison et al 2000) are involved in progesteroneinduced AR. Progesterone also changes motility parameters (Yang et al 1994) and enhances hyperactivation in human (Sueldo et al 1993) and hamster spermatozoa (Noguchi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…These results show that tight regulation of ion entry by ion channels is critical to sperm function. Although there is little doubt as to the importance of calcium homeostasis in sperm motility and fertilization (7)(8)(9)(10)(11)(12), the function of the plasma membrane Ca 2ϩ /calmodulin-dependent Ca 2ϩ ATPase (PMCA) 1 during this process remained enigmatic.…”
mentioning
confidence: 99%